An Analysis of Logical Fallacy on Prabowo Subianto's Argumentation during 2019 Indonesia Presidential Debate - Warman, Jaka Satria; Hamzah, Hamzah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2020)
There have been a considerable number of studies of fallacy concerning with presidential debates in Western countries particularly on American presidential debates. However, the study is still rarely concerned with presidential debates in Eastern countries particularly Indonesia. Therefore, this study attempted to find the types of logical fallacies on Indonesian presidential debates committed especially by one of the presidential candidates, Prabowo Subianto, during 2019 Indonesian presidential debates. The data are utterences containing logical fallacies and the source of the data is the transcripts of four debate videos. The theory of fallacy classification by Damer (2009) was employed in this research. There were thirteen types of fallacies found in this research. The most dominant one was the fallacy of false alternatives with the percentage of 31.25%, and followed by the fallacy of drawing the wrong conclusion and appeal to irrelevant authority with the percentage of 15.62% and 9.37% respectively.